A ceraphronid wasp in Early Miocene amber from the Dominican Republic (Hymenoptera: Ceraphronidae) - Engel, Michael S. (Novitates Paleoentomologicae, 2013)
The first fossil of the parasitoid wasp family Ceraphronidae (Ceraphronoidea) is described and figured.  Ceraphron ceuthonymus Engel, new species, is described from Early Miocene (Burdigalian) amber from the Dominican Republic and distinguished from its close congeners.  A brief summary of the fossil record of Ceraphronoidea is provided.